Effects of vegetation cover on soil heat flux in the southern Yukon Territory - Harris, Stuart A. (ERDKUNDE, 1998)
Net radiation on bright sunny days during August in the southern Yukon represents 25% of the potential radiation. However, in the shade, net radiation is negative, even at 1400 hours. Heat flux into the substrate beneath different vegetation covers over peat in late August in the southern Yukon Territory showed marked differences, depending on the plant species and vegetation structure. Single vegetation canopies or mats showed the least negative values and the highest diurnal amplitudes. Multiple canopies of vegetation provided more negative values but lowest diurnal ranges of heat flux. June measurements made immediately after snowmelt showed higher heat fluxes and diurnal ranges than those in August, except for Cladina stellaris, which scarcely changed. This may be due to the relatively small amounts of moisture held by such mats, or to its higher albedo. Sphagnum was still moist in August, so it was not a major factor in insulating the ground from summer heat. Five degree slopes with different aspects have profound differences in heat flow when compared to horizontal surfaces on silt loams at Fox Lake. Thus flat-topped landforms such as peat plateaus will require fewer field measurements for modelling than landforms with sloping surfaces. Once again, shrub-covered surfaces showed greater heat loss than those with a single mat. These factors must be examined when carrying out meso- or micro-scale studies of heat flow. These observations may also explain why the slopes on perennial mounds do not collapse and degrade due to the insulating effect of the thicker winter snow covers. It is also clear that vegetation covers with multiple canopies and a mat of lichens can insulate the underlying permafrost during short periods with mean annual air temperatures above 0°C. Clearly, mean annual air temperature based on the average of the highest and lowest daily air temperature measured 2 m above a grassy horizontal surface is of relatively limited use as an indicator of the actual heat flow at the ground surface.